1996
DOI: 10.1042/bj3170059
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and inhibition of hydroxyapatite formation by mineralized tissue proteins

Abstract: Many proteins found in mineralized tissues have been proposed to function as regulators of the mineralization process, either as nucleators or inhibitors of hydroxyapatite (HA) formation. We have studied the HA-nucleating and HA-inhibiting properties of proteins from bone [osteocalcin (OC), osteopontin (OPN), osteonectin (ON) and bone sialoprotein (BSP)], dentine [phosphophoryn (DPP)] and calcified cartilage [chondrocalcin (CC)] over a wide range of concentrations. Nucleation of HA was studied with a steady-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
470
1
14

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 556 publications
(505 citation statements)
references
References 47 publications
20
470
1
14
Order By: Relevance
“…The inorganic core of dehydrated CPN samples has however been found to be amorphous, based on experimental results from a range of techniques including electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy (FTIR) and X-ray absorption spectroscopy (Cross et al 2005;Holt et al 1982Holt et al , 1996Holt et al and 2009Hunter et al 1996;Holt and Hukins 1991). Drying or radiation damage could nonetheless destroy crystalline order in the CPN.…”
Section: Introductionmentioning
confidence: 99%
“…The inorganic core of dehydrated CPN samples has however been found to be amorphous, based on experimental results from a range of techniques including electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy (FTIR) and X-ray absorption spectroscopy (Cross et al 2005;Holt et al 1982Holt et al , 1996Holt et al and 2009Hunter et al 1996;Holt and Hukins 1991). Drying or radiation damage could nonetheless destroy crystalline order in the CPN.…”
Section: Introductionmentioning
confidence: 99%
“…These Gla residues are thought to facilitate adsorption of osteocalcin to hydroxyapatite (10,14,15) and are located in the central, conserved portion of the molecule. In contrast, its N-terminal part exhibits considerable sequence variation (4,8,9,13).Initial studies showed that osteocalcin binds strongly to hydroxyapatite crystals (7) and affects mineral formation and mineral crystal growth in solution (16,17). Several studies also suggested a role for osteocalcin as a matrix signal for the recruitment and differentiation of osteoclasts (18-21).…”
mentioning
confidence: 99%
“…Because of its unique calcium binding properties, early functional studies suggested that osteocalcin controlled the nucleation or deposition of mineral in bone (7)(8)(9)(10). However, more recent evidence indicates that osteocalcin is not related to events which allow mineral deposition to occur but, rather, that it participates in regulation of mineralization or bone turnover.…”
mentioning
confidence: 99%